Mechanical Behaviour of Materials, Mechanics of Fibre-Reinforced Composites - Clyne T.W; Kiatlertpongsa Joey; DoITPoMS, University of Cambridge
En este conjunto de animaciones se revisan los principios de los materiales compuestos reforzados con fibra. Comprende los siguientes elementos:Axial stiffness with transverse loading. Reuss ModelCoupling stresses in long fibre compositesStress-strain graph in fibre composites: lower failure strain in matrixStress-strain graph in fibre composites: lower failure strain in fibreInaccuracies in axial strength approachInaccuracies in transverse strength approachCalculation of vaulting pole bendingFibre pull-out and other energy absorbing mechanismsElastic constants for a laminaStiffness of laminates with different number and direction of pliesCalculation of the elastic constants for different loading angles in a laminateTensile-shear interaction: model for variation of ηxyx with loading angleUniaxially loaded cross-ply laminate behaviour under loadFailure of a single lamina: maximum stress criterionFailure of a single lamina: the Tsai-Hill criterionTransverse stiffness with transverse loading. Reuss ModelStiffness of long fibre composites: comparison of different models